Discourse studies: Between social constructionism and linguistics. A critical overview - Cap Piotr (Topics in Linguistics, 2019)
This paper gives a critical overview of the analytical approaches dominating the field of discourse studies in the last three decades, from the perspective of their philosophical and formative bases: social constructionism and linguistics. It explores different conceptions of the theoretical nexus between these two bases leading to the emergence of three distinct yet complementary strands of thought (i-iii). The paper starts with poststructuralist views of discourse salient in (i) Laclau and Mouffe’s Discourse Theory. Laclau and Mouffe’s assumption that no discourse is a closed entity but rather transformed through contact with other discourses is taken as the introductory premise to present a large family of (ii) critical discourse studies, characterized as text-analytical practices explaining how discourse partakes in the production and negotiations of ideological meanings. Finally, the paper discusses (iii) three recent discourse analytical models: Discourse Space Theory, Critical Metaphor Analysis and the Legitimization-Proximization Model. These new theories take a further (and thus far final) step towards consolidation of the social-theoretical and linguistic bases in contemporary discourse studies. The empirical benefits of this consolidation are discussed in the last part of the paper, which includes a case study where the new models are used in the analysis of Polish anti-immigration discourse.